Management of non-communicable disease prevention at district level in Malaysia - R., Diana; M., Safrin; Nada; Abdul Manaf, Rosliza (Community Health Society Malaysia, 2019)
Background: The Non –Communicable Disease (NCD) unit in Malaysia has had much focus in recent years as its country undergoes a major epidemiologic transition with the rise in the four largest contributors of NCD deaths namely cardiovascular disease, cancer, diabetes and chronic respiratory disease. In line with reducing the burden of NCD both for the patient and healthcare, the district health office plays a vital role in managing disease prevention through adequate planning, focusing on the implementation of primary, secondary and tertiary prevention and monitoring the health of the population. Materials and Methods: A literature review was conducted through online database search such as Google Scholar and PubMed to identify articles that were related to the current management of non-communicable disease prevention. Initial keywords used were district health management, non-communicable disease, prevention and Malaysia. The reference list was also reviewed for related articles including some that were handpicked. Result: Healthcare system in Malaysia is performed as a top down exercise whereby most of the national planning is conducted at federal level by the Ministry of Health. However, at the ground level, the district health office needs to conduct situational analysis to identify the needs and challenges of the local community within their jurisdiction. The management of NCD prevention is focusing on the implementation of actions through primary, secondary and tertiary prevention levels that fall within the role of health professionals and health care providers in primary care, hospitals and community services environment. Conclusion: Community empowerment and health education are important components in primary prevention of NCD. Early diagnosis and prompt treatment for NCD provided at the district level will stop the progression of the disease, leading to a better prognosis. Tertiary prevention in the form of rehabilitation at district level reduces and limits the disability and impairment related to NCD.